Effect of human pharmaceuticals common to aquatic environments on hepatic CYP1A and CYP3A-like activities in rainbow trout (Oncorhynchus mykiss): An in vitro study - Burkina, Viktoriia; Sakalli, Sidika; Pilipenko, Nadezhda; Zlabek, Vladimir; Zamaratskaia, Galia (Chemosphere, 2018)
This study examined the ability of several human pharmaceuticals to modulate hepatic piscine CYP-mediated monooxygenase activities. Effects of six pharmaceuticals: diclofenac, sulfamethoxazole, tramadol, carbamazepine, venlafaxine and nefazodone, were investigated in vitro in rainbow trout hepatic microsomes. The reactions of 7-ethoxyresorufin-O-deethylase (EROD) and benzyloxy-4-trifluoromethylcoumarin-O-debenzyloxylase (BFCOD), were used as markers for hepatic CYP1A and CYP3A-like activities, respectively. Our results showed that EROD and BFCOD activities were both affected by nefazodone. Nefazodone inhibited EROD in a dose dependent manner and was found to be a potent non-competitive inhibitor of EROD with a Ki value of 6.6 μM. BFCOD activity was inhibited non-competitively in the presence of nefazadone with Ki value of 30.7 μM. BFCOD activity was slightly reduced only by the highest concentration of carbamazepine. Diclofenac, sulfamethoxazole, tramadol, and venlafaxine did not affect the activity of either EROD or BFCOD. We further exposed microsomal fraction to mixtures of six pharmaceuticals to investigate potential inhibition. The results showed that EROD and BFCOD activity was inhibited on 94% and 80%, respectively at higher tested concentration. To our knowledge, this is the first report to demonstrate an inhibitory effect of nefazodone on hepatic CYP1A and CYP3A-like proteins in rainbow trout.
Keywords: játra; Antidepressant; jaterní mikrozomy; Oncorhynchus mykiss; Microsomes, Liver; léčivé přípravky; Cytochrome P-450 CYP1A1; Humans; cytochrom P-450 CYP1A1; Pharmaceutical Preparations; Cytochrome P450; cytochrom P-450 CYP3A; Fish microsomes; Mixture of compounds; lidé; zvířata; Triazoles; Liver; piperaziny; Water Pollutants, Chemical; Cytochrome P-450 CYP3A; Piperazines; triazoly; Animals; Inhibition; chemické látky znečišťující vodu